Application of Internet Plus nursing services in the management of chronic diseases among the elderly (“互联网+护理服务”在老年慢性病患者管理中的应用) - LI Jiao (李娇); CAI Miaomiao (蔡苗苗) (中西医结合护理)
With the increasingly significant aging trend of China's population, the number of patients with chronic diseases is constantly rising, and the characteristics of chronic diseases determine that most of the treatment and rehabilitation time is spent in the family and community, and traditional nursing services have been difficult to adapt to the changes in patients' needs. "Internet Plus nursing service" uses "Internet+" information technology to accurately connect the diversified medical service needs of the people through the mode of "online application and offline service". This paper summarizes the application status of "Internet Plus nursing service" in elderly chronic patients in China, including relevant policy support, service items, patient participation and application effects, and analyzes the existing problems in home nursing services for elderly chronic patients based on "Internet Plus nursing service" in China. The aim is to provide guidance basis for clinical home nursing services for elderly patients with chronic diseases, help patients better understand the "Internet Plus nursing services", reduce the travel burden of patients, achieve high-quality continuous nursing services, and make more elderly patients with chronic diseases benefit from it. (随着人口老龄化趋势加重, 老年慢性病健康服务成为当下社会关注的重点, 传统的护理服务模式已经难以适应患者需求的变化。“互联网+护理服务”利用“互联网+”信息技术, 通过“线上申请、线下服务”的模式, 精准对接人民群众多样化的医疗服务需求。本研究就“互联网+护理服务”的概念、相关政策、服务项目、服务方式等进行综述, 旨在帮助医护人员、患者更好地了解“互联网+护理服务”, 减轻患者医疗负担, 提高延续性护理服务质量。)